Exosomal miRNAs involvement in pathogenesis, diagnosis, and treatment of rheumatoid arthritis - Mahvash Sadeghi; Jalil Tavakol Afshari; Afsane Fadaee; Mohammadreza Dashti; Fatemeh Kheradmand; Sajad Dehnavi; Mojgan Mohammadi (Heliyon)
Rheumatoid arthritis (RA) is the most common chronic autoimmune arthropathy worldwide. The initiation, and progression of RA involves multiple cellular and molecular pathways, and biological interactions. Micro RNAs (miRNAs) are characterized as a class of small non-coding RNAs that influence gene expression at the post-transcriptional level. Exosomes are biological nano-vesicles that are secreted by different types of cells. They facilitate communication and signalling between cells by transferring a variety of biological substances, such as proteins, lipids, and nucleic acids like mRNA and miRNA. Exosomal miRNAs were shown to be involved in normal and pathological conditions. In RA, deregulated exosomal miRNA expression was observed to be involved in the intercellular communication between synovial cells, and inflammatory or regulatory immune cells. Furthermore, circulating exosomal miRNAs were introduced as available diagnostic and prognostic biomarkers for RA pathology. The current review categorized and summarized dysregulated pathologically involved and circulating exosomal miRNAs in the context of RA. It highlighted present situation and future perspective of using exosomal miRNAs as biomarkers and a specific gene therapy approach for RA treatment.